Contribution of natural killer cells in innate immunity against colorectal cancer - Ghazvinian, Zeinab; Abdolahi, Shahrokh; Tokhanbigli, Samaneh; Tarzemani, Shadi; Piccin, Andrea; Reza Zali, Mohammad; Verdi, Javad; Baghaei, Kaveh (Frontiers in Oncology, 2023)
Natural killer cells are members of the innate immune system and promote cytotoxic activity against tumor or infected cells independently from MHC recognition. NK cells are modulated by the expression of activator/inhibitory receptors. The ratio of this activator/inhibitory receptors is responsible for the cytotoxic activity of NK cells toward the target cells. Polarization and degranulation of lysosomal granules are highly dependent on the cytoskeleton of NK cells. Colorectal cancer (CRC) is the second most common cause of death in the world and is incidence is about 2 million new cases per year. Metastatic CRC is always accompanied by a poor prognosis with less than three years of overall survival. Chemotherapy and surgery are the most adopted treatments. Besides, targeted therapy, immune checkpoint blockade is a novel approach to CRC treatment. In these patients, circulating NK cells are a prognostic marker. Allogeneic NK cell therapy has been widely investigated within clinical trial. In this review we will discuss NK related approaches including CAR NK cells, cell-based vaccines, mono clonal antibodies and immunomodulatory drugs against CRC tumoral cells.